2015
DOI: 10.1177/0022022115575737
|View full text |Cite
|
Sign up to set email alerts
|

Black and Minority Ethnic Groups’ Perception and Experience of Early Intervention in Psychosis Services in the United Kingdom

Abstract: In the United Kingdom, Black and minority ethnic (BME) service users experience adverse pathways into mental health care. Ethnic differences are evident even at first-episode psychosis; therefore, contributory factors must operate prior to first presentation to psychiatric services. This study examines the cultural appropriateness, accessibility, and acceptability of the Early Intervention (EI) for Psychosis Services in Birmingham (the United Kingdom) in improving the experience of care and outcomes for BME pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(134 citation statements)
references
References 34 publications
(43 reference statements)
3
131
0
Order By: Relevance
“…Given that the development status of a country has been identified as a potential contributing factor to recovery outcomes, cultural diversity within countries should also be considered and this may be an important gap in our current understanding of subjective recovery. A study in the United Kingdom, though not specifically about subjective recovery, found that people from minority ethnic groups link or relate mental illness to something supernatural, and therefore prefer to deal with it in their own traditional way (Islam, Rabiee, & Singh, ) which affects their recovery. Less representation of minority ethnic groups in different recovery studies (Law et al, ; Law, Neil, Dunn, & Morrison, ) limits the global view of the issue.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the development status of a country has been identified as a potential contributing factor to recovery outcomes, cultural diversity within countries should also be considered and this may be an important gap in our current understanding of subjective recovery. A study in the United Kingdom, though not specifically about subjective recovery, found that people from minority ethnic groups link or relate mental illness to something supernatural, and therefore prefer to deal with it in their own traditional way (Islam, Rabiee, & Singh, ) which affects their recovery. Less representation of minority ethnic groups in different recovery studies (Law et al, ; Law, Neil, Dunn, & Morrison, ) limits the global view of the issue.…”
Section: Discussionmentioning
confidence: 99%
“…A third limitation relates to the illness beliefs under measure and the overall bio‐psycho‐social conceptualization of psychosis suggested. The model, whilst representing best knowledge and practice, remains embedded with western psychiatry and not necessarily at one with other illness perspectives that may also be considered to play an important role in some BAME groups and cultures (Banerjee & Roy, ; Islam et al, ; Suhail & Cochrane, ). Furthermore, exploring the contribution of ethnic membership on specific carer outcomes would be an important area to explore.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, the meanings assigned to illness symptoms and labels can differ between and within carer and patient groups, depending on ethnic membership (Patel, Chawla, Krynicki, Rankin, & Upthegrove, 2014;Upthegrove, Atulomah, Brunet, & Chawla, 2013;Zafar, Syed, & Tehseen, 2008). Qualitative investigations of BAME service users and carers accessing early intervention in psychosis services suggest an increased need for better information about illness course and recovery outcomes (Islam, Rabiee, & Singh, 2015).…”
Section: Carer Illness Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Data relating to the needs of individuals recovering from FEP were present in all other articles; however, needs were not the primary phenomenon being investigated. 6,8,[20][21][22][23][24][25][26][27][28] For each of the domains of the SCNF, both broad categories of need and specific needs were identified. The majority of these needs are present in Fitch's outline of the SCNF.…”
Section: Resultsmentioning
confidence: 99%